Grid Sebagai Penerapan Prinsip Kesinambungan Dalam Teori Gestalt - Petrus Gogor Bangsa (Ars: Jurnal Seni Rupa dan Desain, 2011)
In layout on the design has its elements, ie: text, visual and invisible. As an invisible element, the grid have a role as carriers of regularity. Grid has a function and characters such as line as in design element. Although not visible, but humans are naturally going to consider it as an element that exists, as the application of the principle of continuity in Gestalt psychology.Keywords: layout elements, grids, Gestalt psychology